Co-metabolism of nonylphenol ethoxylate in sequencing batch reactor under aerobic conditions - Ekdal, Alpaslan; Okutman Tas, Didem; Zengin, Gulsum Emel; Onay, Irmak Batı; Olmez Hanci, Tugba; Orhon, Derin; Cokgor, Emine (Springer Science and Business Media LLC, 2022)
The study evaluated the co-metabolism of nonylphenol polyethoxylate (NPEO) within a main substrate stream subjected to biodegradation in an activated sludge system. Peptone mixture simulating sewage was selected as the synthetic substrate. As a novel approach, the NPEO concentration was magnified to match the COD level of the peptone mixture, so that co-metabolism could be evaluated by respirometry and modeling. A sequencing batch reactor (SBR) set-up at high sludge age to also allow nitrification was operated for this purpose. A long acclimation phase was necessary to start NPEO biodegradation, which was completed with 15% residual by-products. Modeling of respirometric data could identify COD fractions of NPEO with corresponding process kinetics for the first time, where the biodegradation of by-products could be interpreted numerically as a hydrolysis mechanism. Nonylphenol diethoxylate (NP2EO) was observed as the major by-product affecting the biodegradation of NPEO, because NPEO and NP2EO accounted for 60 to 70% of the total soluble COD in the solution during the course of biological reactions. The co-metabolism characteristics basically defined NPEO as a substrate, with no appreciable inhibitory action on the microbial culture both in terms of heterotrophic and autotrophic activities.
Keywords: Biodegradation, Environmental; Sewage; Peptones; Ethylene Glycols